Carry-over of persistent organochlorine pesticides through placenta to fetus - Waliszewski Stefan M.; Aguirre Angel A.; Infanzón Rosa M.; Siliceo José (Instituto Nacional de Salud Pública, 2000)
OBJECTIVE: As a consequence of environmental exposure, organochlorine pesticides accumulate in lipid rich-tissues such as maternal adipose tissue and partition to maternal blood serum and umbilical blood serum. To establish their distribution in the human body, the concentration gradients of organochlorine pesticides between these compartments were determined. MATERIAL AND METHODS: Maternal adipose tissue, blood serum and umbilical blood serum samples from 64 volunteers admitted for cesarean delivery at Hospital Benito Coquet Lagunes were studied in Veracruz during 1997 and 1998. The pesticide residues were determined by gas chromatography and results obtained from different sample groups were analyzed using Pearson correlation coefficients and simple lineal regression. RESULTS: Significant results expressed on fat basis of organochlorine pesticides indicate that 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) levels are higher in maternal adipose tissue (4.51 mg/kg DDE and 1.27 mg/kg pp'DDT), maternal blood serum (4.45 mg/kg DDE and 0.78 mg/kg pp'DDT), and umbilical blood serum (4.70 mg/kg DDE and 0.88 mg/kg pp'DDT), due to greater affinity of DDT for lipids. CONCLUSIONS: The statistical evaluation of results and the pairing of samples analyzed indicate that absorbed organochlorine pesticides cross the placental barrier and reach a balanced state between mother and fetus.